Induction of an acrosomal process in Toxoplasma gondii: Visualization of actin filaments in a protozoan parasite - Shaw, Michael K. (The National Academy of Sciences, 1999)
The invasive stages of Toxoplasma gondii, an Apicomplexan parasite, actively invade their host cells in an actin-dependent way. However, despite containing biochemically significant amounts of actin, actin filaments have never been observed in these parasites. Jasplakinolide, a membrane-permeable actin-polymerizing and filament-stabilizing drug, induced the polymerization of actin filaments at the anterior end of each tachyzoite in association with the conoid, where they formed, in many cases, a prominent membrane-enclosed apical projection reminiscent of acrosomal processes of invertebrate sperm. These jasplakinolide-induced filaments decorated with myosin subfragment 1, demonstrating unequivocally that they were indeed actin. Jasplakinolide-treated tachyzoites were unable to invade host cells, but once the drug was removed the parasites were able to enter host cells. Actin polymerization at the apical end of the parasite is consistent with the role of the apical end in host-cell invasion powered by a jackhammer-like extension and retraction of the conoid complex coupled to the secretion and rearward capping of surface proteins.